Coordinated control strategy of electro-hydraulic braking for energy regeneration. (March 2020) - Pei, Xiaofei; Pan, Hao; Chen, Zhenfu; Guo, Xuexun; Yang, Bo
Abstract: This paper presents a coordinated control strategy of electro-hydraulic braking for distributed electric vehicles. To meet braking regulations requirements in conjunction with the characteristic of the in-wheel motor and power battery, the feasible region of the maximum regenerative braking torque and the evaluation indexes of the electro-hydraulic braking are proposed. In order to realize the optimal objective of energy regeneration and braking stability, the coordinated control of electro-hydraulic braking can be taken as a global distribution problem of two braking torques — hydraulic and regenerative. The optimal distribution coefficients are achieved by the genetic algorithm (GA) under different braking conditions. Moreover, the braking intention of the driver is integrated into the weight coefficients to achieve a dynamic distribution. The results of simulation show that the proposed strategy not only has better performance of energy regeneration and braking stability than I curve distribution, but also satisfies the characteristics of the driver's braking behavior under corresponding situations.